Investigating ozone episodes in Portugal: a wavelet-based approach - Monteiro, Alexandra (2018)
During the summer season, ozone concentrations regularly exceed the legislation limits in the North of Portugal, namely at Douro Norte monitoring station. The origin of such ozone episodes has been widely reported in several studies although uncertainties regarding its origin still remain. This work intends to investigate how the ozone concentrations measured at the Douro Norte nearest stations, located at west and east directions, are related to those measured at Douro Norte by means of coherence and phase transformations methods. The episodes were selected according to the magnitude of the hourly ozone peaks and the occurrence of exceedances of the threshold value at least in two sites. The results point out that 60 % of the selected episodes highlight significant dependence between Douro Norte station and the other two monitoring sites, with different phase signal and a delay range from 2 to 4 h.